Media Pembelajaran RWC Book terhadap Prestasi Belajar Matematika Siswa - Witri Khalidah; Muhammad Hayyun (Universitas Pendidikan Indonesia (UPI), 2022)
This research is motivated by the existence of low mathematics learning achievement, students who are slow in reading, writing or calculating will make the learning process ineffective which will cause problems that cannot be solved. The main purpose of this study was to determine the effect before and before the application of the RWC Book learning media and to find out how much influence the RWC Book learning media had. The research method used in this study is quantitative, the type of method used is the Pre-Experimental method. The survey design used in this survey is One Group Pretest-Posttest. The results of this study indicate a significant influence on student achievement. this is evident from the results of calculations that show the results of the t test obtained Sig. (2-tailed) of 0.000 0.05, it can be said that there is an average influence on student learning achievement for the Experiment Class Pre Test with the Experiment Class Post Test after being given treatment.